Effects of particle sizes on the properties of binderless boards made from rattan furniture waste - Ahmad, Zuraida; Tajuddin, Maisarah; Maleque, Md. Abdul; Halim, Zahurin (Penerbit Universiti Sains Malaysia, 2019)
Rattan furniture had produced high amount of wastes with different particle sizes that could be used in manufacturing binderless boards (BB), which were the boards that reduced or excluded the use of synthetic resins in board production. Therefore this research is executed to study the effect of particle sizes of rattan furniture waste (RFW) on the properties of BB produced via hot-pressing technique. The pressing parameters is fixed at the temperature of 180°C, pressing load of 1.5 MPa and holding time of 5 min using different particle sizes of 50, 100, 250 and 500 μm and denoted as BB50, BB100, BB250 and BB500 respectively. All the BB samples underwent bending, internal bonding, thickness swelling, water absorption and morphological testing. The BB50 had the best properties with modulus of rupture (MOR) of 24.3 MPa, internal bonding (IB) of 0.35 MPa, thickness swelling (TS) of 20.2% and water absorption (WA) of 48.2%. scanning electron microscope (SEM) morphology shows the compact and tight bonding among fibres for BB50. In contradict, the BB500 had the lowest values due to weak bonding and occurrence of voids inside the BB. Physical consolidation among the fibres inside BB and degradation of chemical components inside RFW were the anticipated self-bonding mechanism that occurred during the production of BB via this hot-pressing process.